Effect of pH and neutrophil count on the motility and persistence of spermatozoa in the vagina of candidiasis rat models - Iswara, Raja AW.; Hestiantoro, Andon; Budiningsih, Yuli; Werdhani, Retno A.; Birowo, Ponco; Wuyung, Puspita E.; Afandi, Dedi (Narra J, 2024)
Sexual violence is a global issue affecting individuals regardless of their relationship to the perpetrator or the setting. Microscopic examination of spermatozoa from vaginal swabs is crucial in investigating cases of sexual intercourse to determine the time of the crime. Factors such as vaginal pH and neutrophil count influence the motility and persistence of spermatozoa in the vagina, particularly in conditions like candidiasis, highlighting the need for further research in this area. This study aimed to determine the effect of pH and neutrophil count on the motility and persistence of spermatozoa in the vagina with candidiasis. An experimental study was conducted using white rats (Rattus norvegicus) of the Wistar strain, with four male rats providing spermatozoa samples and 32 female rats receiving treatment. The female rats were divided into two groups: the normal group and the candidiasis model group. In both groups, the female rats were given vaginal insemination of spermatozoa. Variables measured included pH, neutrophil count, motility, and persistence of spermatozoa in the vagina. Data were analyzed using the Mann-Whitney test, followed by the Spearman correlation test. The findings revealed that spermatozoa motility lasted up to three minutes in normal rats, whereas in the candidiasis model, it was reduced to two minutes. Additionally, spermatozoa persistence in the vagina lasted up to six days in the normal group compared to up to three days in the candidiasis model. There were significant differences in pH, neutrophil count, motility, and persistence of spermatozoa in the vagina between the normal group and the candidiasis model (all had p<0.001). There was a correlation between pH and neutrophil count with the motility and persistence of spermatozoa in the rat’s vagina (p<0.001). In conclusion, vaginal pH and neutrophil count influence the motility and persistence of spermatozoa in the vagina of candidiasis rat models.